A GIS‐Based GOD Model and Hazard Index Analysis: The Quaternary Coastal Collo Aquifer (NE‐Algeria). Issue 1 (25th September 2018) - Boulabeiz, Mahrez; Klebingat, Stefan; Agaguenia, Siham
Abstract: The quaternary coastal Collo aquifer in northeast Algeria (NE Algeria) marks an important local water resource supporting domestic, industrial and agricultural activities. The aquifer shows signs of contamination due to the existence of various pollution sources, especially nitrogen compounds. Focusing the local identification of key vulnerable zones and related main hazard types for wise future water management, the present study highlights results from a coupled analysis of the well‐established Geographical Information System (GIS)‐based GOD (groundwater occurrence, overall aquifer class, depth to groundwater) hazard index analysis and the COST Action 620 plan. Most prevalent hazard types in the study area were identified as the urban/residential areas without public sewage systems, landfill and agricultural/pasturing areas. Regarding the vulnerability analysis particularly the northern aquifer region is endangered, dominated by high (22.4%) and moderate (27.4%) vulnerability classes. Central, western and southern aquifer regions are characterized by low (23.3%) and very low (26.9%) vulnerability classes. Overall, these GOD‐derived results are in good agreement with earlier results obtained by the more complex DRASTIC approach. Final risk assessment and validation related to 2014/2015 nitrate sampling campaigns indicate that "high risk" and "very high risk" classes only apply to a small part of the study area in the northern sector (8%), whereas the main part (>60%) broadly affecting the central, western and southern sector only bears a low to very low risk of water pollution. Apart from a future‐oriented groundwater abstraction strategy it is recommended to update the evaluation regularly to effectively consider dynamic changes of local anthropogenic activities and hazards. Abstract : Article impact statement : The NE Algerian Collo plain belongs to the hot spot regions adversely affected by climate change and water scarcity.